Are there objective biomechanical symptoms of the knee instability after anterior cruciate ligament injury or it’s reconstruction - Dmitry V. Skvortsov; Alyona V. Altukhova; Sergey N. Kaurkin; Alexander A. Akhpashev (Клиническая практика, 2024)
BACKGROUND: The instability of the knee joint after a rupture of the anterior cruciate ligament and even after its reconstruction remains a pressing problem. The use of a special functional test with fast walking can be considered as a potential tool for verifying this instability.